Youth and subculture as creative force : creating new spaces for radical youth work - Skott-Myhre, Hans Arthur (University of Toronto Press, 2008)
"Radical youth work is gaining popularity as a means of teaching adults how, in collaboration with youth, they can challenge dominant ways of knowing. This study uses two particular subcultures, skinheads and punks, to explore how constructions of subcultures in time, language, space, body practice, and identity offer alternative ways of understanding youth-adult relationships. In doing so, it investigates youth work as a radical political process and suggests anew approach to current subculture theory. In Youth and Subculture as Creative Force, Hans Arthur Skott-Myhre interviews six youths who identify themselves as members of either punk or traditional skinhead subcultures. He discusses the results of these interviews and demonstrates how youth perspectives have come to inform his understanding of himself as a youth worker and scholar. Youth subcultures, he argues, have considerable potential for improving relations between youths and adults in the postmodern capitalist world. Drawing on Marxist, Foucauldian, and postmodernist theory, Skott-Myhre uses the subjective formations outlined in his study to offer recommendations for constructing legitimate radical youth work that takes into account the perspectives of young people"--